Exploring the Interface between Poverty and Climate Change Adaptation in Coastal Communities of Bangladesh - Noman, Abu Saleh Mohammad (Journal of Posthumanism, 2025)
Climate change is an exquisite threat for Bangladesh where population density is high, more than 50 million people still live under poverty line, many of them reside in remote, ecologically fragile coastal belts and develop their livelihood-based own adaptive strategies to climate change. The study explores the interface between poverty and climate change adaptation in coastal communities of Bangladesh. The study finds that climate change and poverty in coastal community of Bangladesh are correlated. Climate change intensifies their poverty, exacerbates their livelihood vulnerabilities, and makes them the poorest of the poor. On the other hand, poverty has devastating negative impacts on their adaptation strategies to climatic impacts on their lives and livelihood assets. Being deprived of public institutional support for adaptation to climate change, the destitute coastal people take loan from private sectors which augment their state of poverty, work as a net of exploitation instead of support-generation activities.